2014
DOI: 10.1055/s-0034-1370890
|View full text |Cite
|
Sign up to set email alerts
|

African Trypanosome-Induced Blood–Brain Barrier Dysfunction under Shear Stress May Not Require ERK Activation

Abstract: Keywords► African trypanosomes ► blood-brain barrier ► brain microvascular endothelial cells ► trypanosoma brucei rhodesiense ► shear stress ► MAPK AbstractAfrican trypanosomes are tsetse fly transmitted protozoan parasites responsible for human African trypanosomiasis, a disease characterized by a plethora of neurological symptoms and death. How the parasites under microvascular shear stress (SS) flow conditions in the brain cross the blood-brain barrier (BBB) is not known. In vitro studies using static model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previously, it was shown that intraluminal flow is critical for development and maintenance of BBB phenotype in vivo and in vitro resulting in high barrier tightness [8, 35, 36]. Various in vitro dynamic models (DIV-BBB) were developed to understand the role of laminar or pulsatile shear stress on BBB endothelial function and dysfunction in various pathological conditions including inflammation and stroke [31, 37, 38, 39, 40]. For instance, exposure of immortalized hCMEC/D3 cell line to pulsatile flow strongly potentiates the barrier integrity, with 10-fold increase in TEER values compared to static cultures [41].…”
Section: Shear Stress and Cell Differentiationmentioning
confidence: 99%
“…Previously, it was shown that intraluminal flow is critical for development and maintenance of BBB phenotype in vivo and in vitro resulting in high barrier tightness [8, 35, 36]. Various in vitro dynamic models (DIV-BBB) were developed to understand the role of laminar or pulsatile shear stress on BBB endothelial function and dysfunction in various pathological conditions including inflammation and stroke [31, 37, 38, 39, 40]. For instance, exposure of immortalized hCMEC/D3 cell line to pulsatile flow strongly potentiates the barrier integrity, with 10-fold increase in TEER values compared to static cultures [41].…”
Section: Shear Stress and Cell Differentiationmentioning
confidence: 99%
“…[ 272 ] It is thought that these improvements to barrier properties arise from the interplay between the Wnt/B‐catenin signaling cascade with hypoxia‐induced factor 1a (HIF1a) signaling, which Park et al were able to show through upregulation of HIF1a in their hypoxic conditions. [ 274 ] This offers a potential work‐around for the induction of hypoxic conditions, as HIF1a‐mimetic or stabilizing compounds can be used in addition to or instead of the use of a hypoxic chamber.…”
Section: Hypoxiamentioning
confidence: 99%
“…MSCs in prokaryotes have been postulated to participate in quorum sensing, biofilm formation and regulation of virulence factors [19][20][21][22]. Protozoan pathogens, like trypanosomes and apicomplexans, are subjected to mechanical forces associated with shear stress in the bloodstream [23,24], extravasation [25,26] and invasion of tissues required for establishing persistent infection [27][28][29][30][31]. While it is clear that mechanical cues modulate the parasite life cycle and behavior, the molecular mechanism underlying sensing and triggering of the responses required for survival is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs in prokaryotes have been postulated to participate in quorum sensing, biofilm formation, and regulation of virulence factors ( Siryaporn et al, 2014 ; O'Loughlin et al, 2013 ; Thomen et al, 2017 ; Prindle et al, 2015 ). Protozoan pathogens, like trypanosomes and apicomplexans, are subjected to mechanical forces associated with shear stress in the bloodstream ( Harker et al, 2014 ; Sumpio et al, 2015 ), extravasation ( Laperchia et al, 2016 ; Coates et al, 2013 ), and invasion of tissues required for establishing persistent infection ( Barragan et al, 2005 ; Barragan and Sibley, 2002 ; Capewell et al, 2016 ; Trindade et al, 2016 ; Mattos et al, 2019 ). While it is clear that mechanical cues modulate the parasite’s life cycle and behavior, the molecular mechanism underlying sensing and triggering of the responses required for survival is unknown.…”
Section: Introductionmentioning
confidence: 99%